Evaluation of cropping method for perennial ratoon rice: Adaptation of SALIBU to triple-cropping in Vietnam - Oda, Masato (F1000Res, 2020)
Background: Generally, the yield of ratoon rice is at most 50% of the main crop. However, a cropping method “SALIBU” achieved more yield than the main crop and enables the perennial cropping. Although the SALIBU method is implementing 10 additional management practices to conventional method in Indonesia, the effect of each management practice is unclear. Methodology: We evaluated the effect size using an L (16) orthogonal array design pot experiment in triple-cropping rice in Vietnam. The robustness was checked by duplicating the experiment under standard and poor conditions. Results and Discussion: Positive large effects were shown in the poor conditions only.  Cutting twice most affected the number of ratoon tillers. Importantly, the effect was positive under poor conditions but negative under standard conditions. Late irrigation had a robust negative effect. No treatment is effective in the triple-cropping of standard conditions. The SALIBU includes practices with unstable, negative, or minimal effects. The unstable effects show the interaction with the condition. The practices that have negative effects should exclude. Using practice on small effect size should depend on a cost-benefit analysis. Conclusions: No additional practice is effective for changing the triple-cropping to perennial ratoon cropping except harvesting near the ground. However, further work will be conducted to clarify the interaction between cutting twice and the cultivation condition.